If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1(2x-6)=3(5x+4)
We move all terms to the left:
-1(2x-6)-(3(5x+4))=0
We calculate terms in parentheses: -(3(5x+4)), so:We get rid of parentheses
3(5x+4)
We multiply parentheses
15x+12
Back to the equation:
-(15x+12)
-1(2x-6)-15x-12=0
We add all the numbers together, and all the variables
-15x-1(2x-6)-12=0
We move all terms containing x to the left, all other terms to the right
-15x-1(2x-6)=12
| 42y-4y^2=90 | | 3^(5x/4-2)=7 | | 42y-4y^=90 | | x÷3=6 | | -47-6x=81-14x | | F(3a+8)=-5(3a+8)-14 | | 2x2-3x+7=0 | | 55^2+x^2=110^2 | | 1.9=k1 | | 24=3(v=3)-3(v-4) | | 3x+5=18x-3 | | 3x2+2x+5=0 | | 3z+12=3 | | X+2/6-x-3/3=0 | | -18=5y+7 | | -23-12x=41-10x | | -20=-8+4w | | -10x-5=-155 | | -36-13x=72-9x | | 3(4x-8)=7(2x+6) | | 32y-15y=-7 | | 8y-5/7y+1=5/4 | | -3x-86=89-8x | | 4+2u=14 | | √6x+16=x | | 7m+12=3m+4 | | (x-0.04x)=2.12 | | 3(2x+4)-1=2(3x-9)+2 | | 2x-89=175-9x | | 16=8+2h | | 5(c-1)^2=40 | | 6=3n*5 |